A proteomic analysis identifies higher AHSG (Alpha-2-HS-glycoprotein) in saliva of oropharyngeal cancer patients – A potential salivary biomarker - Anu Jain; Aafaque Ahmad Khan; Rajandeep Kaur; Roshan K Verma; Jaimanti Bakshi; Aditi Chatterjee; Amanjit Bal; Sushmita Ghoshal; Arnab Pal (Oral Oncology Reports)
Objective: Oropharyngeal cancer (OPC) is one of the most prevailing cancers worldwide with squamous cell type representing the major cases. OPC has a poor survival rate which is majorly attributed to late presentation of the disease with non-availability of a suitable tumor marker as one of the major reasons associated. This study was designed to identify a potential salivary biomarker for OPC using proteomics approach. Materials and methods: OPC cases were enrolled in different cohorts depending on the tobacco consumption habits as smokers, chewers, smokers and chewers and no tobacco consumers. Healthy controls without any tobacco consumption habits were enrolled simultaneously. Tandem Mass Tag based relative quantification was done to identify the cancer related dysregulated proteins. Dysregulated proteins were validated further in a larger cohort of cases and controls. Furthermore, the tissue expression of AHSG was analysed using the TCGA data available on cBioportal and GEPIA2. Results: 171 proteins were identified of which 135 proteins were dysregulated with ≥2-fold change. Differential expression of proteins in different OPC study cohorts was observed. 15 candidate proteins were selected for validation after analysing the data. AHSG (alpha-2HS-glycoprotein) was one of the candidates, validated in a separate larger cohort of cases and controls and was found to be significantly elevated in cases. AHSG was also found to be upregulated in the tumor tissue of HNSCC patients and patients with low AHSG were found to have the better overall survival outcome in comparison to the cases with higher AHSG. Conclusions: AHSG levels are elevated in saliva of OPC cases compared to non-OPC healthy controls. This expression pattern of AHSG should be evaluated further as a potential biomarker for OPC.